Deuterium retention in RAFM steels after high fluence plasma exposure. (August 2017) - Martynova, Y.; Möller, S.; Rasiński, M.; Matveev, D.; Freisinger, M.; Kiss, K.; Kreter, A.; Unterberg, B.; Brezinsek, S.; Linsmeier, Ch.
Abstract: Deuterium retention and detrapping behavior in the ferritic-martensitic steels EUROFER'97 and P92 after exposure to plasma at high fluences ≥ 10 26 D/m 2 was studied using thermal desorption spectroscopy (TDS), supported by nuclear reaction analysis. Low-temperature irradiation at 450 K and fluences ≥ 10 26 D/m 2 with low impact energy D + / D + +He + ions of 40 eV at PSI-2 resulted in a deuterium inventory of 7–18 × 10 19 D/m 2 predominantly at depths ≥8.6 µm. Helium admixture led to a reduction of total D retention in both steels, irrespective of surface erosion and composition. The deuterium spectra of both steels displayed one D2 desorption peak at ∼ 540–570 K and HD maxima at 540–590, 700–730 and 900–930 K. It is suggested that deuterium is mostly retained in the bulk of steel material on interfaces of carbide precipitates and on grain boundaries. Highlights: Deuterium retention in RAFM steel EUROFER'97, steel P92, pure iron and tungsten was measured after exposure to deuterium/helium plasma at fluences ≥ 10 26 D/m 2 . Exposure resulted in D retention for steels in the 10 19 D/m 2 range predominantly at depths ≥8.6 µm. The steels studied exhibited similarities in D detrapping behavior and dependence on He admixture. Surface composition and morphology are assumed not to play a critical role in D retention, which is mostly attributed to carbide precipitates and grain boundaries in steel bulk material.